The Impact of Renewable Energy Consumption on the Economic Growth of the ASEAN Countries - Fadilah, Sri; Lestari, Rini; Sahdan, Mohd Hadafi; Khalid, Ahmad Zamil Abdul (International Journal of Energy Economics and Policy, 2020)
The foremost purpose of the study is to explore the impact of renewable energy consumption (REC) on the economic growth of ASEAN countries. Data were extracted from the World Bank and ASEAN Energy Information Administration (EIA). The “Generalized Method of Moments (GMM)” approach has been used by using the STATA software for the analysis. The results unprotected that the REC and non-renewable energy consumption (NREC), growth in labor force and capital stock has positive nexus with the economy growth of the ASEAN countries. These findings provide the guidelines to the regulators that they should make the policies for the REC and NREC that increase the economy growth of the world. Keywords: Economy Growth, Renewable Energy, Non-renewable Energy, Growth of Capital, Growth of Labor Force, ASEAN countries JEL Classifications: Q1, N7 DOI: https://doi.org/10.32479/ijeep.10589